Răspunsuri

2014-10-18T15:07:44+03:00
 x^{3} -   3x^{2} + 2x  \geq 0
  x( x^{2} -3x +2)
   x^{2} -3x +2 =0
 Δ=b la 2 - 4ac = 9-8=1    x_{1} 
 =3+1/2=2    x_{2} 
 =3-1/2=1 Facem tabel de semne si ai semnul - intre 1si 2 si + in rest Rezulta x ∈( -infinit;1) reunit cu ( 2; infinit)
[x^{3} - 3x^{2} + 2x \geq 0 [tex] x( x^{2} -3x +2) [/tex] [tex] x^{2} -3x +2 =0 [/tex] Δ=b la 2 - 4ac = 9-8=1 [tex] x_{1} [/tex] =3+1/2=2 [tex] x_{2} [/tex] =3-1/2=1 Facem tabel de semne si ai semnul - intre 1si 2 si + in rest Rezulta x ∈( -infinit;1) reunit cu ( 2; infinit)
...
Nu apare cum trebuie nu?